2014
DOI: 10.1037/a0037190
|View full text |Cite
|
Sign up to set email alerts
|

Selective influence of working memory load on exceptionally slow reaction times.

Abstract: The rate of exceptionally slow reaction times (RTs), described by the long tail of the RT distribution, was found to be amplified in a variety of special populations with cognitive deficits (e.g., early-stage Alzheimer's disease, attention-deficit/hyperactivity disorder, low intelligence, elderly). Previous individual differences studies found high correlations between working memory (WM) and parameters that characterize the magnitude of the long-RT tail. However, the causal direction remains unknown. In 3 cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 84 publications
(152 reference statements)
2
40
0
Order By: Relevance
“…Thus, though most commonly conceptualized as indexing stimulus encoding and motor preparatory time, Ter should also represent the portion of the RT that is spent refreshing memory items, particularly in a situation in which no additional time is allotted for refreshing (i.e., when there are no explicit gaps left between stimuli; Figure 1). This assumption is not without precedent, as previous studies utilizing evidence accumulation models have similarly proposed and demonstrated that Ter can capture WM operations, including task rule retrieval (Shahar Teodorescu, Usher, Pereg & Meiran, 2014; Schmitz & Voss, 2012). In a complex span task where no time is explicitly left open for refreshing between stimuli (as in the current experiment), this assumption allows cognitive load in each condition and for each individual to be estimated by subtracting the proportion of the mean RT taken up by nondecision processes from 1 (cognitive load = 1 - Ter /RT).…”
Section: Diffusion Model-based Measurement Of Speed and Cognitive Loadmentioning
confidence: 99%
“…Thus, though most commonly conceptualized as indexing stimulus encoding and motor preparatory time, Ter should also represent the portion of the RT that is spent refreshing memory items, particularly in a situation in which no additional time is allotted for refreshing (i.e., when there are no explicit gaps left between stimuli; Figure 1). This assumption is not without precedent, as previous studies utilizing evidence accumulation models have similarly proposed and demonstrated that Ter can capture WM operations, including task rule retrieval (Shahar Teodorescu, Usher, Pereg & Meiran, 2014; Schmitz & Voss, 2012). In a complex span task where no time is explicitly left open for refreshing between stimuli (as in the current experiment), this assumption allows cognitive load in each condition and for each individual to be estimated by subtracting the proportion of the mean RT taken up by nondecision processes from 1 (cognitive load = 1 - Ter /RT).…”
Section: Diffusion Model-based Measurement Of Speed and Cognitive Loadmentioning
confidence: 99%
“…For reaction-times analyses, error and post-error trials, ten first trials in each condition and the first trial after each recess were discarded. Reaction-times below 200ms or above 3.5 SDs from the participant's mean in the respective condition were considered as outliers and thus omitted [PROCEDURAL WORKING MEMORY TRAINING] 15 (Schmiedek et al, 2007;Shahar et al, 2014). For the mean-RT, we found strong evidence for lack of transfer effects (see Figure 3).…”
Section: Procedural Working Memory (Near Transfer)mentioning
confidence: 98%
“…A battery of 6-choice-RT tasks was used. In each task, participants were asked to follow a set of six stimulus-response rules, and identify a target using a manual response (Shahar, Teodorescu, Usher, Pereg, & Meiran, 2014) . Three tasks were used:…”
Section: Procedural Working Memory (Near Transfer)mentioning
confidence: 99%
See 2 more Smart Citations